Design of a Web Based Decision Support System to Determine the Study Program for New Students at the Faculty of Technology Battuta University - Sianipar, Erika T.; Ruziq, Fahmi; Sridewi, Nurmala (PT. Technology Laboratories Indonesia (TechnoLabs), 2024)
The admission of new students at the Faculty of Technology, Universitas Battuta faces challenges in placing students in study programs that align with their potential, interests, and talents. The placement process, often conducted manually, can result in mismatches between students and their chosen programs, negatively impacting academic performance and student satisfaction. This study aims to design and develop a web-based Decision Support System (DSS) using the SAW method. The research findings indicate that this DSS is effective in determining study programs by considering three normalized criteria. The system successfully provides accurate recommendations for new students, thereby reducing subjectivity and enhancing the accuracy of student placement.